ANALISIS KRITERIA INTELLIGIBLE, PLAUSIBLE, DAN FRUITFUL MELALUI PEDAGOGI MATERI SUBJEK (PMS) PADA PEMBELAJARAN USAHA DAN ENERGI - Muhammad Ripki Rinaldi; Dedi Kuntadi; Rena Denya Agustina (UIN Sunan Gunung Djati Bandung, 2016)
The learning process is inseparable from the interaction between the teacher, students, and subject matter. Learning is said to be good if it can describe or express learning activities in totality. One approach that can reveal learning in totality is the Subject Material Pedagogy (PMS). PMS considers that learning is a phenomenon of discourse that is able to teach subject matter in a teachable (easily taught) and accessible (easily accessible) format for students that contain intelligible, plausible, and fruitful criteria. The purpose of this study is to determine the intelligible, plausible, and fruitful criteria and the relationship between the three in learning business and energy. The method used in this research is to use the discourse analysis method. This research was conducted in MAN 2 Garut with a sample of class X MIA 4 students. The results showed that the intelligible criteria were 60%, the plausible criteria were 20%, the fruitful criteria were 12%, and without the response were 8%. The relationship between intelligible, plausible, and fruitful criteria on business and energy learning shows that students can reach the fruitful criteria if the students have reached the intelligible and plausible criteria.